PENGARUH SELEKSI DAN PELATIHAN TERHADAP PRESTASI KERJA PADA PT. NUTRICIA INDONESIA SEJAHTERA CABANG JAMBI - Sakinah AS (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
This experiment in doing to analyze the influence of selection and training to work performance on pt .Indonesian welfare nutricia the branch of jambiType of reserach is quantitive survey research properties for descriptive purposes and explanatory. This study using the population with the employees as many as 30 people . data analysis technique used is multiple regressing analysys with path analysis by using SPSS.The influence of selection on work performance on pt .Indonesia nutricia prosperous the branch of jambi in partial influential positive and significance , namely the influence of directly to 7.07 % , while indirect effect is of 18.78 % and the influence of direct and indirect leadership is on the performance of 25.85 % 3 .The influence of training on work performance on pt .Indonesia nutricia prosperous the branch of jambi partial influential positive and significant , which is directly to 61.46 % , while indirect effect is of 18.78 % and the influence of total direct and indirect leadership is on the performance of 80.24 % 4 .The result of testing simultaneously influence the selection of ( x1 and x2 pelatihankerja ( ) on work performance  y in together is of 106,09 %Keyword :Selection, training and work performance